Effects of antibiotic prescribing for respiratory tract infection on future consultations in primary care: a systematic review and meta-analysis - Tom Marshall; Amanda Lambert; Ibrahim Adamu; Safiyya Bello; Fatima Aminu Abdulmalik (BMJ Open)
Objectives Prescribing antibiotics may reinforce patients’ beliefs that antibiotics are needed and increase future consultations for similar symptoms. This review determines the effect of antibiotic prescribing for respiratory infections in primary care on future reattendance.Design A systematic review and meta-analysis of randomised controlled trials (RCTs) and cohort studies and reported following Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Participants were adults or children presenting with respiratory infection in primary care.Data sources MEDLINE (Ovid), PubMed, Embase, the Cochrane Central Register of Controlled Trials, clinical trial registries and grey literature sources were searched from inception until 6 February 2024.Eligibility criteria Eligible studies included open-label RCTs or cohort studies of antibiotics compared with no antibiotics in adults or children with respiratory infections. The outcome of interest was reattendance at least 28 days after the initial consultation.Data extraction and synthesis Two reviewers independently screened, selected, assessed the quality and extracted data. Separate meta-analyses were presented for RCT and cohort studies and a combined meta-analysis of all studies.Results We identified 2128 records and reviewed 48 full texts, of which five met the inclusion criteria. These reported three RCTs (1207 randomised to antibiotics, 672 controls) and three cohort studies (209 138 exposed to antibiotics, 46 469 controls). In the meta-analysis of RCTs, relative risk (RR) of reattendance with antibiotics was 1.10 (95% CI: 0.99 to 1.23), and in cohort studies, RR was 1.21 (95% CI: 0.94 to 1.49). An important limitation is that most studies were in UK primary care.Conclusion Evidence suggests prescribing antibiotics for acute respiratory tract infections in primary care probably modestly increases future reattendance for similar conditions. Reducing antibiotic prescribing may help decrease demand for primary care.PROSPERO registration number CRD42023470731.